Representación de patologías en la cerámica precolombina durante los periodos Formativo Tardío y Desarrollo Regional en la costa del Ecuador. - Rivas, Daniel (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2023)
Paleopathology allows bioanthropologists to approach the diseases and clinical conditions suffered by past societies caused by genetic factors and their interaction with the environment or other external factors. The results of this first approximation to the representation of pathologies in the iconography of the pre-Columbian cultures of the coast of Ecuador during the Late Formative and Regional Development periods allow us to know which were the diseases that affected these societies and to hypothesize how determined they were diseases caused by sociocultural factors giving a more complex meaning to the suffering of these conditions. Likewise, the results of the identification could suggest that some of the pathological markers seen in bone remains found in archaeological contexts had different etiologies, such as porotic hyperostosis and its relationship with Bartonellosis.